SISTEM PENGUBURAN DI GUA DAN CERUK DI KOLAKA UTARA SULAWESI TENGGARA - Bernadeta AKW (WalennaE, 2010)
From the Archaeological excavation along the karsts region in the northern to southern of Northern Kolaka, Southeast Sulawesi, there's many evidence of past burial activities. The findings from the test pit consist of human skeletons, teethes, glass beads, bronze bracelets, and foreign ceramics that associate with the bier. The whole findings found from the cave and shelters provide a description of burial system that used by the society communally. The remains of the burial that spread and the caves and the shelters at North Kolaka was the character of prehistoric tradition. The burial tradition is a part of Neolithic culture that is die Austronesia's culture which is the ethno-genesis of Indonesian. Dari penggalian arkeologis di sepanjang wilayah karst di utara sampai selatan Kolaka Utara, Sulawesi Tenggara, terdapat bukti aktivitas penguburan di masa lalu. Temuan dari lubang uji terdiri dari kerangka manusia, gigi, manik-manik kaca, gelang perunggu, dan keramik asing yang berasosiasi dengan bier. Seluruh temuan yang ditemukan dari gua dan tempat penampungan memberikan deskripsi sistem penguburan yang digunakan oleh masyarakat secara komunal. Sisa-sisa penguburan yang menyebar di gua-gua di Kolaka Utara adalah karakter tradisi prasejarah. Tradisi penguburan adalah bagian dari budaya Neolitikum yang merupakan budaya Austronesia yang merupakan etno-genesis orang Indonesia.